2018
DOI: 10.1111/gcb.14008
|View full text |Cite
|
Sign up to set email alerts
|

Declines in moth populations stress the need for conserving dark nights

Abstract: Given the global continuous rise, artificial light at night is often considered a driving force behind moth population declines. Although negative effects on individuals have been shown, there is no evidence for effects on population sizes to date. Therefore, we compared population trends of Dutch macromoth fauna over the period 1985-2015 between moth species that differ in phototaxis and adult circadian rhythm. We found that moth species that show positive phototaxis or are nocturnally active have stronger ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 45 publications
(100 reference statements)
3
74
0
Order By: Relevance
“…Ecological traps that result in mortality or reproductive failure are predicted to lead to rapid population decline and ultimately extinction (Kokko & Sutherland, ; Robertson, Rehage, & Sih, ). Long‐term records confirm that positively phototactic macro‐moths (Langevelde, Braamburg‐Annegarn, et al, ) in lit habitats (Wilson et al, ) have undergone disproportionate declines in abundance over the past 50 years.…”
Section: Attractionmentioning
confidence: 84%
“…Ecological traps that result in mortality or reproductive failure are predicted to lead to rapid population decline and ultimately extinction (Kokko & Sutherland, ; Robertson, Rehage, & Sih, ). Long‐term records confirm that positively phototactic macro‐moths (Langevelde, Braamburg‐Annegarn, et al, ) in lit habitats (Wilson et al, ) have undergone disproportionate declines in abundance over the past 50 years.…”
Section: Attractionmentioning
confidence: 84%
“…Our multi‐scale (seven scales: 50–3,200 m radii) analysis approach allows us to pin‐point the spatial scales at which these homogenization processes are happening. Although we predict homogenization to affect both butterflies and macro‐moths, we predict that homogenization will be more pronounced for the nocturnal macro‐moths than for the diurnal butterflies as ALAN is highly correlated with urbanization (Sutton, ) and as nocturnally active moth species have been shown to display stronger negative population trends than diurnal moth species in the Netherlands, which is affected by ALAN at a country‐wide scale (van Langevelde et al, ). Also, we predict that homogenization will be pronounced at larger spatial scales for macro‐moths than for butterflies.…”
Section: Introductionmentioning
confidence: 81%
“…Since our planet is urbanizing rapidly with associated environmental change that is both profound and predictable (Niemelä, ; Seto et al, ), and since Lepidoptera are bio‐indicators of other flying insect taxa (Merckx et al, ), the strong biotic homogenization that we here observed for Lepidoptera in Belgium is a process that is likely to happen to aerial insect taxa in urbanized settings all over the world. Butterflies and moths occur in basically all terrestrial ecosystems, and given their abundance and diversity they play important functional roles as prey items in food webs, as pollinators in diurnal and nocturnal pollination networks, and as herbivores in nutrient cycling (van Langevelde et al, ; Merckx et al, ). Their severe biotic homogenization as a response to urbanization, and the impacts of urbanization on other flying insect taxa, are hence likely to impact ecosystem function and ecosystem services provision in towns and cities across the globe (Noriega et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The most influential factors are habitat loss and degradation, pesticides, and climate change (Deutsch et al, 2008;Sánchez-Bayo & Wyckhuys, 2019) although other factors include disease, invasive species, and light pollution (van Langevelde et al, 2018). The most influential factors are habitat loss and degradation, pesticides, and climate change (Deutsch et al, 2008;Sánchez-Bayo & Wyckhuys, 2019) although other factors include disease, invasive species, and light pollution (van Langevelde et al, 2018).…”
Section: Multifarious Causes Of Insect Declinesmentioning
confidence: 99%